2002
DOI: 10.1002/ijc.10151
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cyclinD1 predicts for poor prognosis in estrogen receptor‐negative breast cancer patients

Abstract: CyclinD1 plays a critical role in regulating cell cycle progression. CyclinD1 mRNA and protein are overexpressed in approximately 50% of primary breast cancer cases. However, its clinical significance as a predictive factor remains unclear. One hundred and seventy-three female patients diagnosed with invasive ductal carcinoma who had undergone a mastectomy (161 patients) or breast-conserving surgery (12 patients) were followed up for 6 -119 months (median 86 months) postoperatively. Immunoreactivity for monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 18 publications
5
56
1
2
Order By: Relevance
“…35 In addition, in our previous study, cyclin D1 ablation in human oral squamous cell carcinoma cells was associated with increased cisplatin chemosensitivity. 22 Although it has been reported that high EZH2 expression is correlated with the up-regulation of cyclin D1 in gastric cancer, pharmacologic inhibition of EZH2 leads to the down-regulation of cyclin D1 levels in skin cancer.…”
Section: Discussionmentioning
confidence: 81%
“…35 In addition, in our previous study, cyclin D1 ablation in human oral squamous cell carcinoma cells was associated with increased cisplatin chemosensitivity. 22 Although it has been reported that high EZH2 expression is correlated with the up-regulation of cyclin D1 in gastric cancer, pharmacologic inhibition of EZH2 leads to the down-regulation of cyclin D1 levels in skin cancer.…”
Section: Discussionmentioning
confidence: 81%
“…High cyclin D1 expression has been associated with less aggressive tumour characteristics including hormone receptor positivity. It has associated with low tumour grade [4,6,7,14], although a few studies have failed to confirm this [3,5,11]. The role of cyclin D1 in breast cancer prognosis remains unclear; some studies show correlation to poor, some to good prognosis, and some have not been able to show any correlation.…”
Section: Discussionmentioning
confidence: 99%
“…High cyclin D1 expression is associated with non-aggressive features in breast cancer including estrogen receptor (ER) positivity [3][4][5][6][7][8]. Estrogen stimulates cyclin D1 expression and cyclin D1 is an important mediator of estrogen stimulation of cell cycle progression [9].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] There are reports that cyclins may play a role in some of the hormone sensitive breast cancer cases that are resistant to tamoxifen and the mechanism of action of tamoxifen is affected by the deterioration of control of cell cycle. [11,12] However there is no consensus in the literature on the role of Cyclin D1 in breast cancer biology and its prognostic and predictive value.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%